Fabrication of CdS/Zn2GeO4 heterojunction with enhanced visible-light photocatalytic H2 evolution activity. (5th November 2019) - Hou, Zhenfei; Zou, Xiaoli; Song, Xiuyan; Pu, Xipeng; Geng, Yanling; Wang, Lei
Abstract: CdS/Zn2 GeO4 (CG) composites were synthesized through the simple hydrothermal process. The crystal structure, morphology and light absorption property of the products were studied in detail. The CG composites showed excellent photocatalytic hydrogen production performance upon visible light illumination. Especially, the CG-3 composite displayed the highest H2 evolution rate of 1719.8 μmol h −1 g −1, which was about 3.80 and 4.28 times higher than the pure CdS and Zn2 GeO4 . Besides, the cyclic stability of the CG-3 composite was also excellent. The PL, photocurrent response and EIS spectra results testified that the efficient separation and transfer of photoinduced charge carriers achieved between CdS and Zn2 GeO4, which could result in the promotion of photocatalytic performance. Moreover, a possible mechanism of H2 generation over CdS/Zn2 GeO4 heterojunction was discussed. The practicable way to construct heterojunction composites would be helpful for the design of other systems with excellent photocatalytic property. Highlights: CdS/Zn2 GeO4 composites are successfully synthesized by the facile hydrothermal process. The CdS/Zn2 GeO4 composites showed excellent photocatalytic performance for H2 evolution under visible-light illumination. The novel binary composite favors the enhancement of light absorption and effective electron-hole separation.